Improving MSME Performance: Strategic Management Accounting, Accounting Information Systems, And Management Control Systems Moderated By Financial Technology - Carlos Pangestu, Juan; Akwila, Karvicha (DINASTI RESEARCH, 2024)
Micro, Small and Medium Enterprises (MSMEs) are one of the strong drivers of the people's economy. Micro, Small and Medium Enterprises (MSMEs) have an important role in the economic and industrial growth of a country, a business entity, especially MSMEs, is required to make changes to increase its competitiveness, this is because many small and medium entrepreneurs start from family / home industries so that their management is not managed properly. Most of the research related to Strategic Management Accounting to date has focused on management accounting practices in manufacturing companies and little attention has been paid to the use of management accounting techniques in MSMEs. Banks are a key component of MSMEs. This study aims to examine the effect of Strategic Management Accounting, Accounting Information Systems, and Management Control Systems on MSME Performance moderated by Financial Technology. This study took the research population from MSME companies in Jakarta, Bandung. The type of data used in this study is primary data which is used as a sample. The research method used in this study is a quantitative research method. The sample was selected using the purposive sampling method. To test the hypothesis, this research uses multiple linear regression analysis. Based on the results of the study, it shows that the variables of Strategic Management Accounting and Accounting Information Systems have a significant effect on MSME Performance, but the Management Control System does not have a significant effect on MSME Performance. Financial Technology strengthens the influence of Strategic Management Accounting and Accounting Information Systems on MSME Performance, but Financial Technology does not strengthen the influence of Management Control Systems on MSME Performance.